Nilai Sosial dan Edukasi dalam Kumpulan Dongeng Suku Mbojo - Kasman (JISOSEPOL: Jurnal Ilmu Sosial Ekonomi dan Politik, 2023)
As a cultural product from an area, fairy tales have many values ​​in it. This study aims to analyze social values and education values ​​of contained in the folklore of the Mbojo tribe. The research method used in this research is the descriptive qualitative method. The research data was taken from the book "A collection of tales of the Mbojo tribe: as teaching material for Indonesian in Elementary Schools," published by the publisher Nathan Indonesia 2020. The data needed in the study were collected through careful reading of the elements of fairy tales contained in the book. The technique used in research is note-taking techniques. The data analysis technique used in this study is to use content analysis techniques. The results of this study indicate that there are five social values ​​and values of character education contained in the book a collection of tales of the Mbojo tribe, including (1) social care; (2) justice; (3) responsibility; (4) cooperation; (5) respect the opinions of others.